Air sea conditions facilitate a transformation of the positive Indian Ocean Dipole with distinct east pole characteristics into an extreme event - Li, Zhi; Xu, Zecheng; Zheng, Yunxia; Fang, Yue (Frontiers in Marine Science, 2023)
The Indian Ocean Dipole (IOD) is one of the dominant interannual variabilities in the Indian Ocean (IO), and an extreme IOD, in particular, has dramatic effects on the weather, agriculture, and ecosystem around it. Therefore, the formation of an extreme IOD has been a worldwide research focus. Among 13 positive IOD (PIOD) events, two type-east and two type-comparable PIODs developed into extreme events during the 1960–2020 period. This investigation focuses on the cause of the formation of the type-east extreme PIOD, as previous studies have discussed the origin of the type-comparable extreme PIOD. Composite analysis showed that, as an entity, the strong East Asian and Australian monsoon (EAAM) may result in an evident easterly wind anomaly around the Indonesian region of the Marine Continent during May to August of the years when type-east PIODs occurred. The easterly wind anomaly associated with the EAAM was stronger in the extreme IOD group, whereas it was relatively weak in the regular group. The difference in the easterly wind anomaly between the extreme and regular groups could result in a vertical motion anomaly by enhancing the anomalous westward current. The stronger vertical motion created an upwelling in the deep-layer cold water, resulting in a more distinct difference in the vertical temperature gradient. All these conditions promoted the transformation of the type-east PIODs that occurred in 1961 and 1994 into extreme events and are indicative of the importance of vertical advection terms in the formation of type-east extreme PIODs. This study reveals the cause of the formation of type-east extreme PIODs, which will be helpful in understanding IOD diversity.